Pendidikan Islam Bagi Perempuan Indigenus Indonesia - Wildan Nuril Ahmad Fauzi; Seka Andrean (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
Since long time ago the position of women became second class in the view of society. Not only in obtaining social status, they also get this diksriminasi in health and education. In this paper aims to discuss some of the things that become unease about Islamic education received by women. Although many islamic leaders are well known, unfortunately the drivers of women's Islamic education in Indonesia are very difficult and rare to find. This research uses library research using philosophical approach. Data collection techniques used in articles are by documentation techniques that collect data material in the form of sources of books in the library, articles related to writings related to research. The results showed that women's standing is needed trobosan and movement proves directly through various things and various fields. The establishment of a girls' early childhood school, to build a university based on Islam that combines it with general science, is able to open the face of women as a figure worthy to be recognized the greatness of Islamic Education received by these women contains a variety of knowledge that is able to improve their position and position as a mother and as a wife.